1978
DOI: 10.1111/j.1471-0528.1978.tb14930.x
|View full text |Cite
|
Sign up to set email alerts
|

The Passage of Fat Emulsion Across the Human Placenta

Abstract: Six patients near term were given an intravenous infusion of a fat emulsion (Intralipid) a few hours before normal delivery or Caesarean section. Six other non-infused patients were studied as controls. Maternal venous and umbilical venous and arterial blood samples were taken at delivery and analyzed for individual fatty acid concentrations in triglyceride, free fatty acid (FFA) and phospholipid fractions. The emulsion, being rich in oleic and linoleic acids, affected the composition of the maternal triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
2

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 40 publications
2
14
1
2
Order By: Relevance
“…Although the EPO supplementation was given subcutaneously, its beneficial effect was similar to that seen clinically with intravenous infusion of a fat emulsion (Intralipid) in pregnancy (Elphick et al 1978). They reported a possible beneficial effect of the linoleic acid (1 8 : 2 n 6)-rich Intralipid in a patient at term whose baby had foetal growth retardation.…”
Section: Discussionmentioning
confidence: 90%
“…Although the EPO supplementation was given subcutaneously, its beneficial effect was similar to that seen clinically with intravenous infusion of a fat emulsion (Intralipid) in pregnancy (Elphick et al 1978). They reported a possible beneficial effect of the linoleic acid (1 8 : 2 n 6)-rich Intralipid in a patient at term whose baby had foetal growth retardation.…”
Section: Discussionmentioning
confidence: 90%
“…The relative contribution of NEFA and TG to total placental flux in human pregnancy is not known, although isotope studies in guinea-pigs indicate that more of the fatty acid in the fetal circulation is obtained from maternal TG than NEFA (Thomas & Lowy, 1987). In vivo studies in humans have confirmed that fatty acids derived from maternal TG are taken up by the placenta and released into the fetal circulation (Elphick et al, 1978). The fact that TG increases much more than the other esterified fractions with gestation suggests that this is the major source of esterified fatty acid for the placenta and this is consistent with the finding of Kuhn & Crawford (1986) that there was no detectable uptake from the maternal circulation of 14 C-labelled AA in the form of PL by the perfused human placenta.…”
Section: Maternalmentioning
confidence: 96%
“…It is likely that lipophilic compounds such as PBDEs move into fetal circulation along with maternal lipids. Experimental analysis of maternal and fetal blood samples and lipid infusion studies indicate that there is an influx of lipids from maternal and placental sources into the fetal circulation (Berghaus et al 1998;Elphick et al 1978;Hendrickse et al 1985). Furthermore, there is a dramatic mobilization of maternal fat stores during the third trimester of gestation (Pipe et al 1979), a period critical to brain development (Porterfield 2000); the biologic significance and bioavailability of PBDEs in fetal circulation during this period of gestation have yet to be determined.…”
Section: Discussionmentioning
confidence: 99%